2014
DOI: 10.1002/iub.1296
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin‐activating enzyme is necessary for 17β‐estradiol‐induced breast cancer cell proliferation and migration

Abstract: The sex steroid hormone 17b-estradiol (E2) regulates breast cancer (BC) cell proliferation and migration through the activation of a plethora of signal transduction cascades (e.g., PI3K/ AKT activation) starting after E2 binding to the estrogen receptor alpha (ERa). The activity of the ubiquitin (Ub)-system modulates many physiological processes (e.g., cell proliferation and migration), and recently, a specific inhibitor (Pyr-41) of the Ub-activating enzyme (E 1 ), which works as the activator of the Ub-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“… 34 , 35 E2-activated ER controls carcinogenesis of breast by using intricate signaling pathways that manages multiple cellular responsibilities, namely angiogenesis, migration, growth and apoptosis. 36 , 37 , 38 ER is principally a protein which acts like a ligand dependent transcription factor. Usually, the E2/ER complexes after fusion and co-regulator enlistment, bind easily to estrogen responding space in the promoter area of targeted genes.…”
Section: Estrogen Exposure and Excess Body Weightmentioning
confidence: 99%
“… 34 , 35 E2-activated ER controls carcinogenesis of breast by using intricate signaling pathways that manages multiple cellular responsibilities, namely angiogenesis, migration, growth and apoptosis. 36 , 37 , 38 ER is principally a protein which acts like a ligand dependent transcription factor. Usually, the E2/ER complexes after fusion and co-regulator enlistment, bind easily to estrogen responding space in the promoter area of targeted genes.…”
Section: Estrogen Exposure and Excess Body Weightmentioning
confidence: 99%
“…As E2-dependent transcription of cyclin D1 is necessary for hormone-dependent induction of cell cycle progression [15,[27][28][29], the ability of E2 to induce cellular proliferation in MCF-7 and ZR-75-1 cells was further evaluated in the presence of carfilzomib. As expected, cell cycle analysis revealed that ICI and carfilzomib administration to MCF-7 and ZR-75-1 cells prevents E2-triggered 1 0 cell cycle progression.…”
Section: Carfilzomib Changes Erα Levels and Perturbs E2-induced Prolimentioning
confidence: 99%
“…As E2‐dependent transcription of both cyclin D1 and Bcl‐2 contributes to the E2‐dependent induction of cell cycle progression (Castoria et al, ; Marino et al, ; Acconcia et al, ; Pesiri et al, ), the ability of E2 to induce cellular proliferation in MCF‐7 cells in which either caveolin‐2 or caveolin‐1 expression was reduced was then evaluated. As expected, E2 treatment increased the number of MCF‐7 control cells but not that of MCF‐7 caveolin‐2‐ and caveolin‐1‐KD cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been previously demonstrated that the regulation of ERα content in different breast cancer cell lines is under the control of E2‐induced extra‐nuclear signaling (i.e., PI3K/AKT activation) (La Rosa et al, ; Pesiri et al, ; Totta et al, , ). Thus, the ability of E2 to activate ERα extra‐nuclear signaling in caveolin‐2‐ or caveolin‐1‐depleted MCF‐7 cells was tested.…”
Section: Resultsmentioning
confidence: 99%